Optimalisasi Edukasi UMKM untuk Pengembangan Ekonomi Lokal di Desa Bataguh Pulai Kupang Kabupaten Kapuas Kalteng - Ana Sofia Herawati; Fanlia Adiprimadana Sanjaya; Dewi Lesmanawati; Teguh Wicaksono; Rr Ariessanty Alicia Kusuma Wardhani; Muhammad Rizky Yazidi; Gulfin Susandi (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
This community service activity aims to optimize education and strengthen the capacity of Micro, Small, and Medium Enterprises (MSMEs) in developing the local economy in Bataguh Village, Pulau Kupang, Kapuas Regency, Central Kalimantan. The MSME potential in this village is quite diverse, including lukah (traditional fish traps), lanjung or woven baskets, kencur powder, crackers, chips, and dodol. However, business development still faces several major challenges such as limited capital, weak market access, low digital literacy, and limited human resource capacity. The implementation method used a participatory approach through initial surveys, training, mentoring, and evaluation stages. The training materials included micro business management, conventional and digital marketing strategies, simple financial bookkeeping, and product and packaging quality improvement. The results of the activity indicate an increase in participants’ understanding of business management, the importance of branding and digital marketing, and awareness of forming joint business groups. This activity has had a positive impact on the motivation and readiness of MSME actors to develop businesses based on local potential. The optimization of MSME education has proven to be an effective strategy in strengthening community-based local economic development.